Shifts in macrophage phenotype at the biomaterial interface via IL-4 eluting coatings are associated with improved implant integration. (January 2017) - Hachim, Daniel; LoPresti, Samuel T.; Yates, Cecelia C.; Brown, Bryan N.
Abstract: The present study tests the hypothesis that transient, early-stage shifts in macrophage polarization at the tissue-implant interface from a pro-inflammatory (M1) to an anti-inflammatory/regulatory (M2) phenotype mitigates the host inflammatory reaction against a non-degradable polypropylene mesh material and improves implant integration downstream. To address this hypothesis, a nanometer-thickness coating capable of releasing IL-4 (an M2 polarizing cytokine) from an implant surface at early stages of the host response has been developed. Results of XPS, ATR-FTIR and Alcian blue staining confirmed the presence of a uniform, conformal coating consisting of chitosan and dermatan sulfate. Immunolabeling showed uniform loading of IL-4 throughout the surface of the implant. ELISA assays revealed that the amount and release time of IL-4 from coated implants were tunable based upon the number of coating bilayers and that release followed a power law dependence profile. In-vitro macrophage culture assays showed that implants coated with IL-4 promoted polarization to an M2 phenotype, demonstrating maintenance of IL-4 bioactivity following processing and sterilization. Finally, in-vivo studies showed that mice with IL-4 coated implants had increased percentages of M2 macrophages and decreased percentages of M1 macrophages at the tissue-implant interface during early stages of the host response. These changes were correlated with diminished formation of fibrotic capsule surrounding the implant and improved tissue integration downstream. The results of this study demonstrate a versatile cytokine delivery system for shifting early-stage macrophage polarization at the tissue-implant interface of a non-degradable material and suggest that modulation of the innate immune reaction at early stages of the host response may represent a preferred strategy for promoting biomaterial integration and success.